2016
DOI: 10.5114/pdia.2016.63297
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma awareness and prevalence of dermoscopic examination among internet users: a cross-sectional survey

Abstract: IntroductionMelanoma presents the greater threat to health the later the disease is detected and treated, although treatment results can be improved by the widespread use of dermoscopy. However, scarce data are available concerning the awareness of dermoscopy and the frequency of its performance in the non-patient population.AimTo assess the awareness of melanoma detection by dermoscopic examination among the audience of a scientific website.Material and methodsRespondents were invited to participate in an onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
3
1
1
Order By: Relevance
“…In another study, it was shown that a larger proportion, 25.4% of participants, had undergone dermoscopy at least once in their lifetime, and nearly 40% had sought advice from a dermatologist or another specialist to assess their pigmented lesions. Furthermore, one-tenth of respondents lacked knowledge about dermoscopy, in comparison to half of the respondents from our own study [21].…”
Section: Discussioncontrasting
confidence: 61%
“…In another study, it was shown that a larger proportion, 25.4% of participants, had undergone dermoscopy at least once in their lifetime, and nearly 40% had sought advice from a dermatologist or another specialist to assess their pigmented lesions. Furthermore, one-tenth of respondents lacked knowledge about dermoscopy, in comparison to half of the respondents from our own study [21].…”
Section: Discussioncontrasting
confidence: 61%
“…In three similar studies (29)(30)(31) it was reported that the participants' knowledge levels about skin cancer were low. However, given the fact that the aforementioned studies were conducted with patients rather than healthcare workers, the importance of the results of the present study becomes even more obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Niestety w Polsce obserwuje się jeden z najwyższych w Europie wskaźników stosunku śmiertelności do występowania (0,49) i więcej przypadków zgonów z powodu czerniaka niż w Unii Europejskiej (odpowiednio 2,0 i 1,6). Powodem może być późna wykrywalność, niezgłaszanie wszystkich przypadków wystąpienia czerniaka, utrudniony dostęp do opieki zdrowotnej i niski poziom edukacji, która ma szczególne znaczenie w tym przypadku [9]. Mimo że według wskaźników rozwoju społecznego Polska należy do krajów wysoko rozwiniętych, nasz system opieki zdrowotnej w porównaniu z krajami sąsiednimi jest oceniany źle zarówno przez pacjentów, jak i lekarzy [10].…”
Section: Omówienieunclassified
“…Unfortunately in Poland despite this, one of the highest mortality-to-incidence rate ratios in Europe (0.49) and more reported deaths from melanoma than the EU (2.0 vs. 1.6, respectively) are observed. This could be explained by late detection, incomplete reporting of new melanoma cases, poor access to health care and educational level which highlights the need for education [9]. Although according to the human development index Poland currently is among highly developed countries and within recent years many modern improvements have been implemented, the health care system compared to other neighboring countries, and also as reported by the citizens, patients as well as doctors, is relatively bad [10].…”
Section: Omówieniementioning
confidence: 99%